Video Iklan Sebagai Media Persuasi Sosial Menyikapi Black Campaign - Asakusuma, Cahirul (Fakultas Desain Universitas Komputer Indonesia, 2023)
The internet as a sign of the times makes technology and information more advanced. One of them is that information can be accessed easily by simply relying on a smartphone. Even now, the political sphere has utilized the internet, especially social media, so that there are many cases of unscrupulous actions. The political case carried in this social persuasion design is the presence of many black campaigns ahead of the upcoming 2024 elections with invalid sources of information spread across various social media. The preparation of this report is certainly based on a political case that befell one of the Presidential Candidates Ganjar Pranowo, namely the spread of black campaigns about him. The design of this social persuasion is an appeal to the public, especially the target audience, to be more vigilant in receiving and sharing news that is not yet valid. This design uses the AISAS method with the aim that the message can be conveyed well to the intended target. This persuasion design is realized into a public service advertisement video supported by other supporting media such as making freebies, posters, billboards, brochures and also not forgetting that it can be accessed through Youtube and Instagram social media which can be accessed via linktree.